Experimental Investigation of Gain Offset Behavior of Feedforward-Controlled WDM AGC EDFA Under Various Dynamic Wavelength Allocations - Kiyo Ishii; Junya Kurumida; Shu Namiki (IEEE Photonics Journal)
Realizing dynamics in the optical layer is becoming more important for efficient optical communication networks such as protection switching in the optical domain or reconfiguring the optical layer to meet traffic fluctuations. This paper experimentally investigates gain offset changes under dynamic optical switching using feedforward-controlled wavelength-division-multiplexing (WDM) automatic gain control erbium-doped fiber amplifiers (EDFAs). Realistic optical switching scenarios are emulated by resolving dynamic routing and wavelength assignment problems. The experimental results demonstrate that channel intensity changes with optical switching and that the intensity changes accumulate as the number of cascaded EDFAs increases. Considering a gain model in wavelength assignment can successfully reduce the channel intensity changes by up to 0.7 dB after five cascaded EDFAs. Effects of gain spectral hole burning on the intensity changes are also discussed.